Effect of channel aspect ratio on chemical recuperation process in advanced aeroengines. (15th March 2017) - Zhang, Silong; Cui, Naigang; Xiong, Yuefei; Feng, Yu; Qin, Jiang; Bao, Wen
Abstract: The working process of an advanced aeroengine such as scramjet with endothermic hydrocarbon fuel cooling is a chemical recuperative cycle. The design of cooling channel in terms of engine real working conditions is very important for the chemical recuperation process. To study the effects of channel aspect ratio ( AR ) on chemical recuperation process of advanced aeroengines, three dimensional model of pyrolysis coolant flow inside asymmetrical rectangular cooling channels with fins is introduced and validated through experiments. Cases when AR varies from 1 to 8 are carried out. In the pyrolysis zone of the cooling channel, decreasing the channel aspect ratio can reduce the temperature difference and non-uniformity of fuel conversion in the channel cross section, and it can also increase the final conversion and corresponding chemical heat absorption. A small channel aspect ratio is beneficial for the chemical recuperation process and can guarantee the engine cooling performance in the pyrolysis zone of the cooling channel. Highlights: Large non-uniformity of conversion is bad for the chemical recuperation. Small channel aspect ratio is beneficial for improving the chemical recuperation effectiveness. Small channel aspect ratio is also beneficial for reducing the engine wall temperature.